Hydride precipitation and stresses in zircaloy-4 observed by synchrotron X-ray diffraction - Santisteban, Javier Roberto (2010)
The grain stresses within hydrides precipitated in rolled zircaloy-4 plates were determined by synchrotron X-ray diffraction experiments using an 80 keV photon beam and a high-speed area detector placed in transmission geometry. Results showed large compressive stresses (360 ± 20 MPa) in the hydrides along the plate rolling direction. The origin of these stresses was investigated by performing hydride dissolution/precipitation in situ for thermal cycles between room temperature and 400 C. A large stress hysteresis was observed, with a steady decrease on heating and an abrupt change on cooling. The observed stresses are explained by the constraint imposed by grain boundaries on the growth of hydride platelets on the rolling–transverse plane of the rolled plates.